Degradation of Polyester Partially Oriented Yarns through Alkaline Hydrolysis Process: A Recent Study - J. Hayavadana (New Approaches in Engineering Research Vol. 12, 2021)
Partially oriented yarn is the feed material for draw texturing process of polyester regular and micro fibres. Quality of POY is the biggest challenge the industry faces as the storage of POY leads to degradation and ultimately the quality of draw textured yarn will be questionable. There fore its necessary to find a method to test the freshness POY and alkaline hydrolysis can be used a tool to study the structure of POY. In this research work an earnest attempt is made to explore the caustic action on polyester POY with different parameters of degradation process. Its for the first time such a study has been made using alkaline hydrolysis as a tool to understand the degradation process. The experimental methodology consisted in selecting different pet poy (both micro and macro denier) and storing in standard conditions as per the standard procedures for degradation to occur and subsequently subjecting the stored materials to alkaline hydrolysis as per the standard procedure given by Zeronian and Collin. The treated samples were characterized for density, critical dissolution time and molecular weight. In all the cases it was found that degradation process has significant effect on these properties as found from weight loss of alkaline hydrolysis process. Further the results obtained were statistically significant.